A Case Study on Human Resource Management Practice of a Sport Organization - Dajnoki, Krisztina; Szabados, György Norbert; Bácsné Bába, Éva (International Journal of Engineering and Management Sciences, 2018)
Human resource with the adequate ability and skills is of decisive importance in all organizations, irrespective of the field of activity in which they operate. It is no different with the life of sports organizations. The human resource management of sports organizations is peculiar which is influenced by, on the one hand, the operating form of an organization, on the other hand, the nature of employment. Those well-known jobs can be also found in the sport organizations which are necessary to operate an organization and carry out the general tasks, at the same time, the amateur or professional athletes turn up as specific human resources. Aim of the study is to explore the specific characteristics of the human resource management of a particular organization, namely Debreceni Egyetem Atlétikai Club Sport Nonprofit Közhasznú Kft. (University of Debrecen Athletic Sport Non-profit Public Benefit Purpose Ltd., hereinafter: DEAC Ltd.), primarily focusing on the traditional HR functions. After reviewing the domestic and international specialized literatures, the practice of the examined sport organization will be described by means of case study, document analysis and managerial interview methods. Based on the results, it can be determined that there is no separate HR manager in case of the examined sport organization, due to its size, but the managing director carries out the tasks as an economic and HR manager in one person. From the aspect of organizational operation, the practice of HR functions is similar to the practice of other SME business organizations, at the same time, the management of athletics as human resources means its specific characteristic where the managements of labour supply, career and talent has other interpretation.